Nordplus Project: Networking, new skills and co-creation in Nordic Higher Education - Harbo, Karen; Jönsson, Karin; Tonning, Anne Sissel Vedvik (Nordic Journal of Information Literacy in Higher Education, 2019)
The Nordplus Project: The Digital University Library, http://library.au.dk/blogs/nordplus Nordplus (NP) is the Nordic Council of Ministers' most important programme in the area of lifelong learning (http://www.nordplusonline.org/) and provides funding for activities and networking projects across the Nordic and Baltic region. This development project has applied for and received funding from the NP2016 and NP2017 programmes – and have applied again in 2018 – Lund University Libraries, University of Bergen Library, and The Royal Library Aarhus University Library. The aim of this project has been to meet and establish partnership with faculty and students as co-creators in the emerging blended learning environments. One important way of doing this has been (NP2016) to develop subject specific digital learning objects, supporting academic skills and students’ digital practice. The project group has leant on the method ABC (Arena Blended Connected) curriculum design, introduced to us by researchers from pedagogical departments at the universities. The NP2017 part of the project is focusing on the implementation and evaluation of the new practice. Regarding evaluation, the project is again leaning on research expertise at the universities, having been introduced to “Argumentativa kursusutvärderingsmodeller” (Carola Aili, Lund University), qualitative research design and mixed methods (Rune Krumsvik, University of Bergen). In addition comes a very important issue; the intercultural aspect of sharing experience and knowledge within the three Nordic organisations of Higher Education. A special session First we will present and discuss not only the products, but also the work processes and various methods used in the projects as well as the benefits of the intercultural Nordic collaboration. The format will we short presentations (pitches and posters) – and discussion. Secondly, the NP18 application includes a plan for extending the existing project network to several Nordic educational settings. Therefore, the project group invites Nordic conference colleagues, who would like to discuss an extended Nordic network, to join this session. The format for this part will be network dating and discussion in an open space framework.